PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKABRAIN-BASED LEARNINGUNTUK MELATIHKAN KETERAMPILAN BERPIKIR KRITIS - Kusumawati, Arie (Lensa : Jurnal Kependidikan Fisika, 2016)
The objective of this research was to develope physics learning materials based on Brain-Based Learningthat are valid, practical, and effective to facilitate student’s critical thinking skills in fluid matter. The learning materials development using 4D development model and have been tested on 10th grade students of  The Senior High School of 1 Kopang, academic year 2016/2017, with one group pre-test post-test design trial development research. Data collection methods used were questionnaires validity, tests and observation, whereas data analysis techniques using qualitative and quantitative descriptive analysis. The results were showed several findings: physics learning materials developed had an average score of validity categorized valid, based on the implementation of the lesson plan is obtained that can be done well, especially on elaboration step. The response was very positive towards learning students, critical categorized for student’s critical thinking skills after the trial of physics materials were develop. Based on the results of this trial can be concluded that developement of physics learning material was valid, practical, and effective to facilitate student’s critical thinking skills.